[Frühere [!] Pulvermagazin Stolzenbergergrund] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia dawną prochownię na Chełmie, zamienioną na dom mieszkalny, 26. 03. 1922 r.